Morfoanatomia, tricomas glandulares e fitoquímica de Lomatozona artemisiifolia Baker (ASTERACEAE - EUPATORIEAE) - uma planta endêmica do Cerrado de Goiás - Trindade, Luma Mota Palmeira (2013)
Morphoanatomy, trichomes glandular and phytochemistry of Lomatozona artemisiifolia Baker (Asteraceae - Eupatorieae) - a plant of endemic of Cerrado of Goiás - The Asteraceae family is widely distributed, having 24,000 species and genera 1600-1700, constituting one of the largest families of phanerogams. In the Cerrado, among phanerogams, is the second largest family in number of species. Among the numerous species of Asteraceae is present Lomatozona artemisiifolia Baker, belongs to the tribe Eupatorieae. The objective of this study was to describe anatomically aerial vegetative organs of this species, characterize the glandular trichomes that occur in these vegetative organs and inflorescences, determine the composition of the oil and perform the phytochemical study of the species, as there is no work on this species which is endemic to the Cerrado. For anatomical study were used apexes, samples of completely expanded leaves and stems. The phytochemical screening was performed with aerial vegetative organs and oil extraction was performed with fresh plant material (aerial vegetative organs). The epidermis is uniseriate covered with a thin cuticle striated and mesophyll is dorsiventral. The stem has uniseriate epidermis, cortex and with angular collenchyma lamellar secretory ducts associated with the cortical parenchyma, sclerenchyma fibers forming ice outside the phloem bundles are collateral. Is the presence of eight types of glandular trichomes on the leaf and stem. We identified the presence of traces of alkaloids, coumarins, traces of digitalis glycosides, saponins, flavonoids and glycosides. In oil extraction were identificandos 21 compounds, the major compounds are γ-muuroleno about 28.81%, the β-germacrene with 18.23%, 12.48% caryophyllene, δ-elemene 8.61%, 7.55% δ-carene, β-ocimene 5.94%.